Efforts to Rejuvenate the Visual Identity of State-Owned Enterprises: Barata Indonesia Based on Gestalt - Telaumbanua, Jovan Putra Jaya; Darmawan, Andreas James (IMAGIONARY, 2025)
Visual identity change is an important aspect of a company's branding strategy to maintain competitiveness and relevance in an ever-evolving industry. Barata Indonesia, as a manufacturing and infrastructure company, redesigned its logo to reflect the company's transformation and future vision. The urgency of this research lies in the company's need to have a more modern, flexible visual identity that is in line with its corporate values. This research uses a qualitative descriptive method with a case study approach. Analysis was conducted on old and new design elements, as well as evaluation of stakeholder acceptance through surveys and interviews. This study aims to provide new enthusiasm and increased commitment to the company's image in the eyes of the public, especially in terms of visual appeal and professionalism. The results of the study show that the new logo is more adaptive to various media, has higher visual appeal, and is able to strengthen the company's professional image. In addition, acceptance of the new logo tends to be positive. The majority of respondents stated that this change increased the perception of the company's innovation and credibility. This positive response shows that rebranding can be an effective strategy in building better relationships with stakeholders. The impact of this research not only helps Barata Indonesia in strengthening its branding and maintaining relevance in its industry, but also provides insight for other companies in implementing effective rebranding strategies to remain competitive in a dynamic market.